Concepções de avaliação no ensino de Língua Portuguesa - Trevisan, Natália Peixoto (2022)
Assessment is a term well known by education professionals, but it is not always an integral element of the teaching and learning process. In addition, the objectives in teaching and evaluating the Portuguese language are not always clear to the Basic Education teacher. Obsolete educational and evaluative practices still permeate Portuguese classes and often do not stimulate reflection on language or improve reading and writing skills effectively. This thesis considers the inseparable relationship between teaching/learning/assessment in Portuguese and starts from the hypothesis that teaching, when considering this inseparability, enhances its results. Based on these ideas, this thesis aims to investigate the conceptions of evaluation of Portuguese Language teachers within the inseparable process of teaching/learning/assessment. For this, a bibliographic research was carried out on the topic formative assessment in Portuguese. In addition to the theoretical investigation, a semi-structured group interview was carried out with teachers of Portuguese Language in Elementary School II about their conceptions of evaluation. As a basis for reflection and data analysis, the idea of inseparability between evaluation/teaching/learning by Fernandes (2006; 2008; 2013) was established, socio-interactionism supporting the conception of language and teaching of Portuguese and the concepts of evaluation proposed by Perrenoud (1999), Black et al. (2018), Scallon (2015), among others. As a result, it was found that the Portuguese language assessment is not always conceived in a procedural, formative and regulatory manner and that the assessment itself is still seen as an instrument of power and arbitrariness. In addition, there is a lack of clarity in the objectives of the assessment, there is an excess of subjectivity around the assessment practice and, often, the absence of clear assessment criteria shared with students. The very concept of teaching the Portuguese language still supports the idea of rules to be transmitted, the prevalence of teaching grammar detached from the text and the hygienist practice of textual production, against the recurring backdrop of a logic guided by external evaluations. As the evaluation concepts dictate the evaluation practices that take place on the school floor, it is concluded that there will only be changes in the forms of evaluation if there is an understanding and change in the professionals' conceptions about their performance in the classroom